2010
DOI: 10.1088/2041-8205/723/1/l117
|View full text |Cite
|
Sign up to set email alerts
|

A Patchy Cloud Model for the L to T Dwarf Transition

Abstract: One mechanism suggested for the L to T dwarf spectral type transition is the appearance of relatively cloud-free regions across the disk of brown dwarfs as they cool. The existence of partly cloudy regions has been supported by evidence for variability in dwarfs in the late L to early T spectral range, but no self-consistent atmosphere models of such partly cloudy objects have yet been constructed. Here we present a new approach for consistently modeling partly cloudy brown dwarfs and giant planets. We find th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
243
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(251 citation statements)
references
References 41 publications
8
243
0
Order By: Relevance
“…Burgasser et al (2002) and Saumon & Marley (2008) found that their socalled Cloudy models could not produce the M-L-T spectral transition with a single value of f sed . This conclusion prompted them to propose a patchy cloud model Marley et al (2010). We have not been able to obtain these models for comparison in this paper.…”
Section: Cloud Formationmentioning
confidence: 93%
“…Burgasser et al (2002) and Saumon & Marley (2008) found that their socalled Cloudy models could not produce the M-L-T spectral transition with a single value of f sed . This conclusion prompted them to propose a patchy cloud model Marley et al (2010). We have not been able to obtain these models for comparison in this paper.…”
Section: Cloud Formationmentioning
confidence: 93%
“…The common classification of the secondary in all of these systems is likely a selection bias, as this subtype lies at the peak of the so-called "J-band bump," the 1 μm brightening from late-L to mid-T likely caused by the depletion of photospheric clouds at the L dwarf/T dwarf transition (Ackerman & Marley 2001;Burgasser et al 2002Burgasser et al , 2013Gelino et al 2008;Marley et al 2010). T5 companions are simply more readily detectable in blended light spectra due to their brighter magnitudes.…”
Section: Physical Properties Of the Wise J0720-0846 Systemmentioning
confidence: 99%
“…It is relevant to cloud formation, rain initiation (see Shaw 2003 for a general review), and the general microphysics (Pruppacher & Klett 1997) of the atmospheres of planets and moons (e.g., Barth & Rafkin 2007;McGouldrick & Toon 2008), and of cool stars and brown dwarfs (Helling & Woitke 2006;Helling et al 2008;Marley et al 2010;Freytag et al 2010).…”
Section: Introductionmentioning
confidence: 99%